Modelling and control of a bio-inspired microgripper. (2nd August 2010) - Madhab, G.B.; Kumar, C.S.; Mishra, P.K.
A biologically inspired microgripper has been considered with its kinematic model. The dynamic model of the gripper has been developed considering the system with its equivalent lumped inertia, stiffness and damping parameters. The biomimetic gripper developed is conceptually similar to an agonist?antagonistic mechanism. This mechanism is most commonly used by almost all crustaceans not only for gripping, but also for cutting, crushing, walking, climbing, etc., where two muscles called agonist and antagonist are working against each other to allow movement in both directions and to stabilise the joint. The mathematical model is then simulated using MATLAB/SIMULINK. Based on the SIMULINK model developed, a PID controller is used for precise position control.